Short rib-polydactyly syndrome: a single or heterogeneous entity? A re-evaluation prompted by four new cases. Issue 1 (February 1985) - Bernstein, R; Isdale, J; Pinto, M; Du Toit Zaaijman, J; Jenkins, T
Abstract : Four cases of lethal short rib-polydactyly syndrome (SRPS) from three non-consanguineous families are described. Radiological features were similar in all four cases and were most consistent with type III SRPS (Verma-Naumoff syndrome), but many differences in external and systemic abnormalities were noted. The considerable overlap of supposedly distinctive features displayed by the three main forms of SRPS is suggestive of a single locus mutation with variable expressivity, particularly for types I and III, possibly related to different mutant alleles and secondary intrauterine modification of the phenotype. All four cases showed anomalous sexual development. In spite of testicular differentiation in all four and a 46, XY karyotype in the two on whom chromosome studies were done, two infants were phenotypic females and two had ambiguous genitalia. A definitive diagnosis of SRPS was made at 26 weeks' gestation in a pregnancy at risk.